EVALUATING THE PREVALENCE AND DISTRIBUTION OF UNREGISTERED EMPLOYMENT IN KOSOVO: LESSONS FROM A 2017 SURVEY (The South East European Journal of Economics and Business, 2019)
Despite the growing recognition that unregistered employment remains a common problem both in South-East Europe and well beyond, there has been little evidence available on its prevalence and distribution. This paper begins to fill that gap by reporting a 2017 large scale national representative survey of 8,533 households in Kosovo. This reveals that 34.6% of all employees are engaged in unregistered employment (i.e., they have no employment contract). A Probit regression analysis reveals significant associations between unregistered employment and individual-, household, employer and job-related characteristics, with unregistered employment significantly more prevalent among men, younger people, single, widowed or divorced, those with fewer years in education, living in rural areas and in larger households, working in construction and services, part-time employees, with shorter employment duration, lower wages, and those in elementary occupations and craft and related trades. The wider theoretical and policy implications are then discussed.